2013
DOI: 10.3168/jds.2012-6383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of internal reference genes for quantitative expression analysis by real-time reverse transcription-PCR in somatic cells from goat milk

Abstract: Reverse transcription (RT) quantitative real-time PCR (qPCR) is the most accurate and easy-to-perform technique to measure the expression level of a selected gene of interest by quantifying mRNA transcripts. The use of reference genes is commonly accepted as the most reliable approach to normalize RT-qPCR data and reduce possible errors generated in the quantification of gene expression. The optimal number and choice of reference genes are experimentally validated for specific tissues or cell types and experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…in the present study) the optimal pair does not include the most stable gene. It may be related to the necessity to compensate for the overexpression of the one reference gene by another one, which is underexpressed in the same group [ 26 ]. Detailed results regarding the intra- and intergroup variation of investigated reference genes calculated by NormFinder are shown as supplementary data ( S4 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…in the present study) the optimal pair does not include the most stable gene. It may be related to the necessity to compensate for the overexpression of the one reference gene by another one, which is underexpressed in the same group [ 26 ]. Detailed results regarding the intra- and intergroup variation of investigated reference genes calculated by NormFinder are shown as supplementary data ( S4 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…The changes in the subpopulation fraction potentially affect the choice of the most suitable reference gene. Accordingly, several studies reported the necessity of finding a suitable reference gene for studying gene expression in milk somatic cells in various species such as goats ( Modesto et al, 2013 ; Jarczak et al, 2014 ), zebu ( Varshney et al, 2012 ), or yaks ( Bai et al, 2014 ). The variation in the subpopulation fraction can also be a problem when using a technique such as RNA Sequencing as it takes into account all the genes expressed in a given sample.…”
Section: The Methodology For Using Mec From Milk To Analyze Mammary Gmentioning
confidence: 99%
“…In addition, the amount of RNA maybe insufficient at times and accurate computation of cell number is often infeasible. Another proposed strategy is to use reference genes in data normalization; this strategy is currently considered a robust approach in most cases [ 8 ]. Reference genes are supposed to be constitutively expressed, and their expression should remain stable irrespective of experimental conditions such as developmental stage, experimental treatment, physiological state and tissue type [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%